Alcohol, drugs and young people : clinical approaches - Gilvarry, Eilish; McArdle, Paul, 1954- (Clinics in developmental medicine ;, 2007)
A comprehensive book dealing with drug, tobacco and alcohol abuse in both children and young people. Presents the facts of drug and alcohol abuse, evidence for prevention and treatment, and reviews of the various types of treatments.